Ковер из подземного царства - Аванесян, Лилия (Зангак-97)
In Armenian “Damsel Frog” folk tale the Prince brings presents to his father from the Other World. There is a carpet among these presents which was handed to him by frogs. The donor frogs are connected with the Other World and with the idea of fertility. The carpet gets its sacred properties owing to the fact of coming from the Beyond, by the fact that it was given by the sacred frogs and owing to the material from which it was made. Wool and sheep’s fleece were the symbols of fecundity. Besides, the process of weaving was considered to be a magic ceremony which also was connected with the Other World.
Keywords: Этнография; Фольклор